2020
DOI: 10.1101/2020.10.28.359919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ViMIC: A Database of Human Disease-related Virus Mutations, Integration Sites and Cis-effects

Abstract: Molecular mechanisms of virus-related diseases involve multiple factors, including viral mutation accumulation and integration of a viral genome into the host DNA. With increasing attention being paid to virus-mediated pathogenesis and the development of many useful technologies to identify virus mutations (VMs) and viral integration sites (VISs), abundant literatures on these topics are available in PubMed. However, knowledge of VMs and VISs is widely scattered in numerous published papers, and the associatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In this study, we found that the D32E and H85Y variants exhibited a significantly higher ability to degrade p53 compared to the E6 wild type for first time ( P < 0.05). However, it is noteworthy that, the same as the previous studies ( 18 , 38 ), the mutation frequency of H85Y is higher in NHSIL patients, indicating that additional mechanisms may be involved in the epithelial transformation process.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we found that the D32E and H85Y variants exhibited a significantly higher ability to degrade p53 compared to the E6 wild type for first time ( P < 0.05). However, it is noteworthy that, the same as the previous studies ( 18 , 38 ), the mutation frequency of H85Y is higher in NHSIL patients, indicating that additional mechanisms may be involved in the epithelial transformation process.…”
Section: Discussionsupporting
confidence: 75%
“…Globally, approximately 350 million people are infected with HBV, and 20%‐30% of chronically HBV‐infected individuals may develop cirrhosis and HCC 33,34 . About 80% of HCC cases are related to HBV infection in China 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard file of virus mutation was collected from our previously developed ViMIC database (Wang et al, 2022), consisting of mutation-related literature in five viruses, HBV, HIV, human papillomavirus (HPV), human T-cell lymphotropic virus type-1 (HTLV1) and Epstein-Barr virus. In this study, the positive samples consisted of 1246 abstracts containing virus mutation information.…”
Section: Virus Dataset Preparationmentioning
confidence: 99%
“…Furthermore, due to the inconsistency of virus mutations and the lack of standard mutation nomenclature, the conventional 'Keyword Search' may be difficult to quickly and non-redundantly get desired mutation information from literature in PubMed. As such, extracting, mining and integrating virus mutation-related information from those extremely large amounts of literature has become an increasingly important task in many downstream applications, such as virus mutation database development (Davey et al, 2014;Wang et al, 2022), immune V C The Author(s) 2022. Published by Oxford University Press.…”
Section: Introductionmentioning
confidence: 99%